Age differences in post-error sequential effect: Insights from a Simon task - Pereiro, A. (2015)
Objetive: After an error the Reaction Time (RT) typically is slower and the subsequent response accuracy improves (Ridderinkhof, 2002). This so called Post-error sequential effect (PESE) must be studied carefully in Simon tasks since most of the errors occur in incongruent trials and therefore it may be confused with the congruency effect (Van der Borght et al., 2014). Some evidence exists for the older adults have an increased RT-PESE (Dutilh et al, 2013) but age differences in the effect evaluated from the accuracy still remains scarce. Method: RT and error number (NEs) in a Simon task performed by 165 subjects were analyzed (mean=53.87; SD=29.85). Five age groups were considered (G1=17-19; G2=20-30, G3=65-74; G4=75-85; G5=85-97). RTs and NEs were Log transformed to yield a normal distribution. Results: A 3x2x5 repeated measures ANOVAs were performed to test age group differences among Consistence level (i.e., neutral, consistent, and inconsistent) and Previous Accuracy (i.e., correct vs wrong response) for RT and NEs. For RT, a significant main effect of Consistence, F(2,119)=139.39; p<.001; ?p 2 =.701; observed power (OP)=1.0, Previous Accuracy, F(1,120)=28.13; p<.001; ?p 2 =.190; OP=1.0, and Age Group, F (4,120)=24.81; p<.001; ?p2 =.453; OP=1.0, factors were found. A significant interaction were also found between Consistence*Previous Accuracy factors, F(2,119)=5.51; p =.005; ?p2 =.085; OP =.844. Bonferroni pairwise comparisons (BPC) pointed to significant higher RTs in incongruent condition than in the other two, despite of the Previous accuracy and, significant higher RTs after wrong responses in neutral and congruent conditions but not for inconsistent condition. For NEs, a significant main effect of Consistence, F(2,121)=243.98; p<.001; ?p 2 =.801; OP=1.0, Previous accuracy, F(1,122)=255.63; p<.001; ?p2 =.677; OP=.929, and Age group F(4,122)=23.91; p<.001; ?p 2 =.440; OP=1.0 factors were found. A significant interaction were also found between Consistence*Age group, F (8,244)=2.10; p=.036; ?p2 =.064; OP=.837, and Consistence*Previous accuracy, F(2,121)=167.51; p<.001; ?p2 =.735; OP=1.0; BPC pointed to significant higher errors in Neutral condition than in the Consistent condition, despite of Previous accuracy. Higher levels of accuracy were found subsequent to wrong responses in all experimental conditions. Conclusions: Our results support the existence of a close relationship between Consistence level and PESE. Interactions of age and PESE were not found.